AN ALGORITHM OF IDENTIFICATION OF THE OPTIMAL COMBINATION OF INTERNAL AND EXTERNAL SOURCES OF SUPPLY FOR THE FORMATION OF THE SYSTEM OF FOOD SUPPLY OF THE ARMED FORCES IN THE ARCTIC ZONE OF RUSSIAN FEDERATION - Ruslan Satvaldovich Zheishev (Science and Innovation Center Publishing House, 2019)
The Arctic group of the Armed Forces of Russian Federation that is being formed now requires stable food supplies. However economic, logistic and climatic conditions of this region make the formation of the system of food supply difficult and require a solution of the problem of optimal combination of food deliveries from internal and external sources.